Análise integrada dos impactos ambientais e riscos ocupacionais na operação de unidades de triagem do Brasil: revisão bibliográfica - Brito, Daniel Oliveira de (Universidade do Vale do Rio dos Sinos, 2016)
The purpose of this study was to integrally evaluate the environmental impacts and occupational risks in material recovery facilities of Brazil. The integrated assessment – based on the synergy between environmental management and health and safety management – used the Failure Mode and Effect Analysis (FMEA) on the main risks and impacts identified at the literature review. 26 risks and impacts were identified, of which 77% were classified as significant, critic or catastrophic. Several risks are arising from the same hazards, but related to different targets (environment, health and safety). Based on the assessment, 39 risk’s control measures were proposed, approaching population’s awareness, adequacy at edification, machines, furniture and equipment, management, training and individual protection equipment. It was found the direct influence of the population is a idiosyncrasy of the environmental impacts and occupational risks in the material recovery facilities.
Keywords: Unidades de triagem; Risco ocupacional; Impacto ambiental; FMEA; Material recovery facilities; Occupational risk; Environmental impacto